Textures, provenances, and transport patterns of sediment on the inner shelf of the East China Sea. (1st January 2022) - Cong, Jingyi; Zhang, Yong; Hu, Gang; Mi, Beibei; Kong, Xianghuai; Xue, Biying; Ning, Ze; Yuan, Zhongpeng
Abstract: Although many studies have been carried out on the mud wedge in the inner shelf of the East China Sea (ECS), the sediment sources and seismic textures of the mud wedge are still unclear and remain controversial. Therefore, this study utilizes grain size and clay mineral analyses of surficial sediment samples and high-resolution sub-bottom seismic profile interpretation to identify the provenance and texture of these mud wedge sediments. The results show that sediment sources on the inner shelf of the East China Sea are mixed by the Yangtze River, small mountainous rivers along the Zhejiang-Fujian, and western Taiwan coasts. The sediments derived from the Ou and Min rivers are mainly concentrated in the shallowest shelf area within a water depth of 20 m which is located north of the Min River Estuary. Their contribution to the estuaries and coastal areas reflects the different sediment transport patterns of the two small mountainous rivers. The thickness of the Holocene mud wedge between Hangzhou Bay and Taizhou Bay is greater than 20 m at a water depth of approximately 10 m. The cause of this phenomenon is possibly related to the presence of the Zhoushan Islands, which are distributed along the Zhejiang coast and appear to effectively trap sediments from the Yangtze River, facilitating sediment accumulation. The findings of this study will help improve our understanding of the sediment transport and deposition mechanism of deposition on the inner shelf of the East China Sea. Highlights: We produced grain size and clay mineral analyses and high-resolution sub-bottom seismic profile interpretation. Sediments derived from small mountainous rivers are mainly concentrated in the shallowest shelf area. The thickness of the Holocene mud wedge is locally greater than 20 m in the shallowest shelf area.